Technological Revolutions - Caselli, Francesco (American Economic Review, 1999)
In skill-biased (de-skilling) technological revolutions learning investments required by new machines are greater (smaller) than those required by preexisting machines. Skill-biased (de-skilling) revolutions trigger reallocations of capital from slow- (fast- ) to fast- (slow- ) learning workers, thereby reducing the relative and absolute wages of the former. The model of skill-biased (de-skilling) revolutions provides insight into developments since the mid-1970's (in the 1910's). The empirical work documents a large increase in the interindustry dispersion of capital-labor ratios since 1975. Changes in industry capital intensity are related to the skill composition of the labor force. (JEL E23 J31 O33)